Restoration of functional network state towards more physiological condition as the correlate of clinical effects of pallidal deep brain stimulation in dystonia - Filip, Pavel; Jech, Robert; Fečíková, Anna; Havránková, Petra; Růžička, Filip; Mueller, Karsten; Urgošík, Dušan (Brain stimulation, 2022)
BACKGROUND: Deep brain stimulation of the internal globus pallidus (GPi DBS) is an invasive therapeutic modality intended to retune abnormal central nervous system patterns and relieve the patient of dystonic or other motor symptoms. OBJECTIVES: The aim of the presented research was to determine the neuroanatomical signature of GPi DBS modulation and its association with the clinical outcome. METHODS: This open-label fixed-order study with cross-sectional validation against healthy controls analysed the resting-state functional MRI activity changes induced by GPi DBS in 18 dystonia patients of heterogeneous aetiology, focusing on both global (full brain) and local connectivity (local signal homogeneity). RESULTS: Compared to the switched-off state, the activation of GPi DBS led to the restoration of global subcortical connectivity patterns (in both putamina, diencephalon and brainstem) towards those of healthy controls, with positive direct correlation over large-scale cortico-basal ganglia-thalamo-cortical and cerebellar networks with the clinical improvement. Nonetheless, on average, GPi DBS also seemed to bring local connectivity both in the cortical and subcortical regions farther away from the state detected in healthy controls. Interestingly, its correlation with clinical outcome showed that in better DBS responders, local connectivity defied this effect and approached healthy controls. CONCLUSIONS: All in all, the extent of restoration of both these main metrics of interest towards the levels found in healthy controls clearly correlated with the clinical improvement, indicating that the restoration of network state towards more physiological condition may be a precondition for successful GPi DBS outcome in dystonia.
Keywords: globus pallidus; Internal globus pallidus; Cross-Sectional Studies; Deep brain stimulation; dystonie; Humans; výsledek terapie; Resting-state functional magnetic resonance imaging; lidé; Connectivity; Deep Brain Stimulation; Globus Pallidus; průřezové studie; hluboká mozková stimulace; Treatment Outcome; Dystonia